Exploring the Potential of Omega-3 Enriched Egg Industry in Indonesia: Production, Consumer Demand, and Competitiveness - S. Mulatsih; I. R. H. Soesanto; Y. Retnani; A. Yani; R. Mutia; A. Tanti (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2024)
People are worried about the health impacts of the cholesterol contained in egg. Various studies show that adding omega-3 to laying feed or drinking water will produce omega-3 eggs that are low in cholesterol. This research aims to determine the potential for developing the omega-3 egg industryin Indonesia. Secondary data (from BPS and related literature), and primary data (from interviewed with sample farmers) were analyzed using revenue cost (R/C) ratio, willingness to Pay (WTP) and descriptives analysis. The findings showed that farmer produced omega-3 eggs from small scale (100 birds) to large scale (50,000 birds). Farmer introduce omega-3 through feed in the form of (1) a mixture of salmon oil with vegetable oil, (2) maggots (Hermetia illucens), and (3) processed fish waste. Each provided R/C ratios of 1.10, 1.34, and 1.52. The competitiveness of the omega-3 egg industry in Indonesia is quite strong, supported by (1) abundant sources of omega-3 supplement feed, (2) increasing demand for omega-3 eggs, (3) supported by feed and the pullet industry (4) low competition of omega-3 eggs producer, and (5) support for stunting reduction programs through protein consumption.